2020
DOI: 10.1002/pat.5139
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐responsive shape memory behavior of poly(styrene‐b‐isoprene‐b‐styrene)/ethylene‐1‐octene copolymer thermoplastic elastomer blends

Abstract: Thermally-triggered shape memory polymers (SMPs) are smart materials, which are capable of changing their shapes when they are exposed a heat stimulant. Blending semi-crystalline and elastomeric polymers is an easy and low-cost way to obtain thermo-responsive SMPs. In this work, novel poly(ethylene-co-1-octene) (PEO) and poly(styrene-b-isoprene-b-styrene) (SIS) thermoplastic elastomer blends were prepared via melt blending method. The morphological, mechanical, rheological properties and shape memory behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…[49][50][51] Molecular architecture or molecular deformation mechanism, is another essential factor in achieving shape memory behavior. 52,53 The molecular architecture of SMEs must consist of net-points (the hard phase or fixed phase) and switching units (the soft phase or reversible phase), which allow the structure to be deformed, maintained, and recovered under applied force and external activation. 54,55 Recently, Chien et al 56…”
Section: Overviews Of Smesmentioning
confidence: 99%
“…[49][50][51] Molecular architecture or molecular deformation mechanism, is another essential factor in achieving shape memory behavior. 52,53 The molecular architecture of SMEs must consist of net-points (the hard phase or fixed phase) and switching units (the soft phase or reversible phase), which allow the structure to be deformed, maintained, and recovered under applied force and external activation. 54,55 Recently, Chien et al 56…”
Section: Overviews Of Smesmentioning
confidence: 99%
“…[97] It has been shown that blending a small crystalline molecule such as a fatty acid or paraffin wax to the elastomer can form SMPs as the crystalline domains can form a thermally responsive solid network (Figure 6). [92,[98][99][100] The strategy allows decoupling of the elastomer network, and a fixing network (small crystalline molecule) and has been applied to fabricate SMPs from a range of polyolefins, including sulfonated EPDM polystyrene/polydiene block copolymers and polyolefin block copolymers. The trigger temperature of these SMPs [101][102][103] can be varied easily by varying the content of the incorporated crystalline moieties.…”
Section: Shape Memory Semicrystalline Elastomers and Designing Them T...mentioning
confidence: 99%
“…[ 97 ] It has been shown that blending a small crystalline molecule such as a fatty acid or paraffin wax to the elastomer can form SMPs as the crystalline domains can form a thermally responsive solid network ( Figure ). [ 92,98–100 ]…”
Section: Shape Memory Semicrystalline Elastomers and Designing Them T...mentioning
confidence: 99%
“…Shape memory polymers (SMPs) are a type of intelligent material that can be fixed with a temporary shape and recover to a permanent shape in response to external stimuli 1 such as temperature, 2,3 light, 4 electricity, 5,6 magnetic field, 7 and solvens 8,9 . SMPs have many advantages such as large deformation, a wide range of stimulation methods, easy processing, easy modification, low cost, and corrosion resistance 10 .…”
Section: Introductionmentioning
confidence: 99%